Selected Papers from PRES'19 The 22nd Conference on Process Integration, Modelling and Optimisation for Energy Saving and Pollution Reduction - KLEMEŠ, Jiří Jaromír; Fan, Yee-Van; Pintarič, Zorka Novak (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Energy is a fundamental social need and plays an essential role in driving economic growth. The emerging economy requires the support of a reliable, affordable, and energy system with low carbon emissions and air pollutants. System design is important in facilitating sustainable development. Various works that aspire to promote sustainable system design by addressing the issues of enhancing energy and environmental performance were presented in the Special Issue (SI) of the 22nd Conference on Process Integration, Modelling and Optimisation for Energy Saving and Pollution Reduction (PRES'19). The contribution can be categorised into four topics focused on modelling, simulation, optimisation, and assessment studies, on the topics of: (a) heat integration and heat transfer, (b) integrated and newly developed heat exchangers, (c) integration of renewables (d) roles in economic and environmental sustainability. This book is complemented with an editorial review, to highlight the broader state-of-the-art development.